2005
DOI: 10.1042/bj20050339
|View full text |Cite
|
Sign up to set email alerts
|

αB-crystallin, a small heat-shock protein, prevents the amyloid fibril growth of an amyloid β-peptide and β2-microglobulin

Abstract: AlphaB-crystallin, a small heat-shock protein, exhibits molecular chaperone activity. We have studied the effect of alphaB-crystallin on the fibril growth of the Abeta (amyloid beta)-peptides Abeta-(1-40) and Abeta-(1-42). alphaB-crystallin, but not BSA or hen egg-white lysozyme, prevented the fibril growth of Abeta-(1-40), as revealed by thioflavin T binding, total internal reflection fluorescence microscopy and CD spectroscopy. Comparison of the activity of some mutants and chimaeric alpha-crystallins in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
141
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(153 citation statements)
references
References 50 publications
12
141
0
Order By: Relevance
“…In Alzheimer brain, αBC binds to AβPP [26], and αBC mRNA is increased (referenced in [26]). In vitro, αBC prevents Aβ fibril growth and spontaneous fibril formation, binds Aβ, and prevents its aggregation [27][28][29]. However, when applied extracellularly to cultured rat neurons, concomitantly with Aβ, αBC increases Aβ cytotoxicity [28], possibly due to αBC's influence in maintaining Aβ in its soluble oligomeric, highly cytotoxic form [28].…”
Section: Discussionmentioning
confidence: 99%
“…In Alzheimer brain, αBC binds to AβPP [26], and αBC mRNA is increased (referenced in [26]). In vitro, αBC prevents Aβ fibril growth and spontaneous fibril formation, binds Aβ, and prevents its aggregation [27][28][29]. However, when applied extracellularly to cultured rat neurons, concomitantly with Aβ, αBC increases Aβ cytotoxicity [28], possibly due to αBC's influence in maintaining Aβ in its soluble oligomeric, highly cytotoxic form [28].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the chaperone activity of αB-crystallin can be easily compared with well-established data on its chaperone activity against amorphously aggregating target proteins. Thus, studies have shown that αB-crystallin inhibits the fibrillation of α-synuclein [48, 83,93], β2-microglobulin [94] (Esposito, Carver, et al, unpublished results), κ-casein [95,96], the ccβ-Trp peptide [95], apoC-II [97], and the prion protein (Ecroyd, unpublished results). In doing so, αB-crystallin acts as a chaperone under a range of solvent conditions, including at pH values as low as 2.5 against β2-microglobulin fibrillation [94].…”
Section: Shsps and Alzheimer's Diseasementioning
confidence: 99%
“…They also found that the toxicity of aggregated DAβ(1-40) and Aβ(1-42) to human brain pericytes was completely abolished by co-incubation with αB-crystallin (at a 1.0: 0.2 molar ratio of DAβ(1-40): αB-crystallin and a 1.0: 0.02 molar ratio of Aβ(1-42): αB-crystallin). Raman et al [94] have reported that the increase in ThT fluorescence associated with fibril formation by the Aβ peptides is completely inhibited by a 1.0: 0.05 molar ratio of Aβ(1-40): αB-crystallin and a 1.0: 0.1 molar ratio of Aβ(1-42): αB-crystallin (αB-crystallin was also found to be more effective at preventing the fibril formation of Aβ(1-40) than αA-crystallin). These authors concluded that no stable complex forms between αB-crystallin and Aβ(1-40), but instead αB-crystallin acts primarily by forming a complex with the fibril nucleus to prevent its growth [94].…”
Section: Shsps and The Aβ Peptidesmentioning
confidence: 99%
See 2 more Smart Citations